Underconfidence and the low-experimentation trap - Tyack, Nicholas; Arouna, Aminou; Dembélé, Urbain; Goeschl, Timo (AWI discussion paper series, 2026)
We study how confidence bias affects investment in learning via experimentation, a mechanism critical for technology adoption under uncertainty. We hypothesize that bias direction and strength predict how willingness to experiment diverges from unbiased agents. We measure revealed and stated demand for experimenting with drought-resistant crop varieties of 1,957 farmers in West Africa, a climate change hotspot. Consistent with our hypothesis, confidence bias strongly predicts willingness to experiment. The effect, however, is driven exclusively by underconfident agents, among whom females are overrepresented. In deteriorating environments, this behavioral friction undercuts effective technology diffusion and risks trapping individuals in maladapted production environments.
Keywords: Graue Literatur